Higher plant diversity promotes higher diversity of fungal pathogens, while it decreases pathogen infection per plant. Issue 7 (1st July 2014) - Rottstock, Tanja; Joshi, Jasmin; Kummer, Volker; Fischer, Markus
Abstract : Fungal plant pathogens are common in natural communities where they affect plant physiology, plant survival, and biomass production. Conversely, pathogen transmission and infection may be regulated by plant community characteristics such as plant species diversity and functional composition that favor pathogen diversity through increases in host diversity while simultaneously reducing pathogen infection via increased variability in host density and spatial heterogeneity. Therefore, a comprehensive understanding of multi‐host–multi‐pathogen interactions is of high significance in the context of biodiversity–ecosystem functioning. We investigated the relationship between plant diversity and aboveground obligate parasitic fungal pathogen ("pathogens" hereafter) diversity and infection in grasslands of a long‐term, large‐scale, biodiversity experiment with varying plant species (1–60 species) and plant functional group diversity (1–4 groups). To estimate pathogen infection of the plant communities, we visually assessed pathogen‐group presence (i.e., rusts, powdery mildews, downy mildews, smuts, and leaf‐spot diseases) and overall infection levels (combining incidence and severity of each pathogen group) in 82 experimental plots on all aboveground organs of all plant species per plot during four surveys in 2006. Pathogen diversity, assessed as the cumulative number of pathogen groups on all plant species per plot, increased log‐linearly with plant species diversity. However, pathogen incidence and severity, and hence overall infection, decreased with increasing plant species diversity. In addition, co‐infection of plant individuals by two or more pathogen groups was less likely with increasing plant community diversity. We conclude that plant community diversity promotes pathogen‐community diversity while at the same time reducing pathogen infection levels of plant individuals.